Alaa Gabbar Nima Al-Sakanani's objections to Ibn Al-Hajib in his explanation of Al-Shafia - التميمي, علاء جبار نعمة (lark, 2020)
The field of drainage remains full of new ones, because it is a vast sea in which scholars excelled, classified the literature, explained and placed footnotes. This research deals with the objections of Al-Sakanani, one of the commentators of Shafi’ah, and from the eighth century scholars.
Keywords: Key words: Ibn al-Hajib - al-Sakaniani - morphological objections - reasoning